The relationship between talent management with performance management in selected public higher learning institutions - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
Higher Learning Institutions (HLIs) in abroad have adopted Talent Management (TM) in the managerial system which leads to Performance Management (PM) in the organization has gone up. In correlation to that, Ministry of Higher Education (MOHE) has taken a proactive action to introduce TM in public HLIs in Malaysia. In hoping to see the PM of public HLIs to go higher, strategies has been created and developed to ensure the level of public HLIs is parallel with those in abroad. Therefore, this research has been conducted to examine the relationship between TM and PM in selected public HLIs. Quantitative method has been used in order to collect a primary data of this research with 714 respondents have been approached to answer a questionnaire in selected public HLIs which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSI) and Universiti Teknologi Mara (UiTM). Information obtained from the descriptive survey has been analyzed by using IBM Statistical Packages Social Sciences (SPSS). Results showed that the relationship between TM and PM in three selected public HLIs were in moderate level whereby USM scored higher correlation as compared to other two public HLIs. As a conclusion, the result of this research will be a benchmark to other public HLIs in Malaysia to strengthen up their strategies in TM in order to boost up the organization. Meanwhile, in three selected public HLIs need to come up with better implementation of TM in order to ensure the relationship of TM and PM is highly interrelated.